Fridavisornas musik: På spaning efter Birger Sjöbergs personstil - Brolinson, Per-Erik; Larsen, Holger (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 1999)
The songs of the Swedish author and composer Birger Sjöberg (1885-1929) occupy a stylistic middleground between folk song and art song. This stylistic ambiguity is reflected in almost every feature of his music: melody, rhythm, harmony and form. Although the songs may have an air of unabitious simplicity, they are often difficult to perform. Several of his songs contain references, sometimes very subtle, to other musical works. At the same time his style is disticntively personal. This essay attempts to investigate his stylistic double nature as well as his uniquely personal traits.